Penerimaan Diri Alumni Anak yang Berkonflik dengan Hukum Pasca Rehabilitasi di Bengkel Jiwa Jember - Istiqomah, Lutfi Nailil; Prafitralia, Anisah; Suryadi, Suryadi (UIN Kiai Haji Achmad Siddiq Jember, 2025)
Self-acceptance is something important for alumni of children in conflict with the law or adult criminal alumni to return to society. Self-acceptance is very much needed for individuals who have committed a crime or violence, which makes the individual have negative feelings, and makes him feel traumatized after the incident to divert these negative feelings to self-acceptance, evaluation, and improvement. This study aims to determine the form of self-acceptance of alumni of children in conflict with the law after rehabilitation at Bengkel Jiwa Jember and the factors that support it. The method used is qualitative research with a case study type, with the aim of achieving intensity in collecting data. The subjects of the study were four alumni of children in conflict with the law who had undergone Rehabilitation at Bengkel Jiwa Jember. The location of the study itself was the residence of each alumni. The results obtained were self-acceptance in the four informants which were summarized in three categories, namely: body acceptance, self-protection from social stigma, and confidence in one's own capacity. The factors that support self-acceptance of research subjects include: understanding of oneself, the absence of obstacles and pleasant attitudes from the surrounding environment, the absence of serious emotional disturbances, having a broad perspective, and parental support.